Comparison of DC-Link Voltage Control Architectures on Grid-Side and Machine Side for Permanent Magnet Synchronous Generator Connected to the Grid. - Molina Gordillo, Steven Xavier (2022)
Energy production through wind power generation systems presents instability mainly due to wind variability the dynamic performance of the DC-Link is necessary for the proper operation of wind power plants using PMSG-based technologies, therefore, it is necessary to guarantee the efficient voltage control in the DC-Link in a back to back topology of the converters used for the energy conversion. This research compares the effect of implementing DC-Link voltage control on the Grid Side Converter versus DC-Link voltage control on the Machine Side Converter. The simulated system consists of a wind turbine coupled to the Permanent Magnet Synchronous Generator, Power Electronic Converters and the grid. Internal current controllers and external DC-link voltage control are designed for each case. The performance of the system against wind speed changes and voltage faults in the grid is evaluated and compared.